361PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN DIVIDEND PAYOUT RATIO SEBAGAI VARIABEL KONTROL - Stella Aurellia Tengjono; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to prove whether the implication of corporate governance has influence on firm value with firm size and dividend payout ratio as control variables. The implication of corporate governance. The implementation of corporate governance measured by using the Corporate Governance Perception Index (CGPI) rating scores that compiled by The Indonesian Institute for Corporate Governance. Meanwhile, firm value measured by Tobin’s Q. This study tested on 93 companies that are listed in the CGPI rating as well as in the Indonesia Stock Exchange during 2001-2015 with a total of 135 observational data. The research result showed that the implementation of corporate governance had no affect on firm value. The result also indicated that firm size had significant negative affect on firm value while the dividend payout ratio had significant positive affect on firm value.